Implementasi UU Nomor 2 Tahun 2004 dalam Menyelesaikan Perselisihan Hubungan Industrial - Agatha Jumiati; Waluyo S Pradoto; Hanindito B R (Medan Resource Center, 2021)
In a work environment or company where disputes are unavoidable. Disputes that occur within the company are known as labor disputes or industrial relations disputes. A labor dispute is a conflict between an employer or an association of employers and a labor union or a combination of labor unions in connection with the absence of a conflicting understanding of the working relationship, working conditions and/or labor conditions. Law Number 2 of 2004 has provided stipulations on measures that can be taken to resolve industrial relations disputes through bipartite negotiations, mediation, conciliation, arbitration and through proceedings at the Industrial Relations Court.